Analisis Pengaruh Biaya Mutu Terhadap Penjualan Produk (Studi Kasus: Pusat Oleh-Oleh Minang di Kota Padang) - Harmelia Harmelia; Devi Edriani (Jurnal Ekonomi dan Bisnis Dharma Andalas, 2019)
This is an empirical research to determine the influence of the independentvariable quality cost to the dependent variable sales.A T-test onprevention cost, valuation cost, failure cost showed significant influence on sales. An F-test on prevention cost,valuation cost, internal failure cost and external failure cost also showed significant influence on sales. Regression analysis was done using the multiple linear regression equation Y = 5316.608 + .988 X1 +.332 X2 + .018 X3 . Regression analysis showedpositive that prevention cost, valuation cost, internal failure cost, andexternal failure cost had a positive influence on sales, which indicates thatincreasing costs of quality leads to increase in sales. A coefficientdetermination test (Kd) showed that 95% of quality cost contributes tosales; the remaining 5% is influenced by factors other than cost of quality